Current scenario of CNG vehicular pollution and their possible abatement technologies: an overview - Trivedi, S.; Prasad, R.; Mishra, A.; Kalam, A.; Yadav, P. (Springer Science and Business Media Deutschland GmbH, 2020)
Compressed natural gas is an alternative green fuel for automobile industry. Recently, the Indian government is targeting to replace all the conventional fuel vehicles by compressed natural gas (CNG) automobiles due to its several merits. Still, the presence of a significant amount of CO, CH4, and NOx gases in the CNG vehicle exhaust are quiet a matter of concern. Thus, to control the emissions from CNG engines, the major advances are under development of and oxidation is one of them in catalytic converter. In literature, the catalysts such as noble and non-noble metals have been reported for separate oxidation of CO and CH4.. Experimentally, it was found that non-noble metal catalysts are preferred due to its low cost, good thermal stability, and molding tractability. In literature, several articles have been published for CO and CH4 oxidation but no review paper is still available. Thus, the present review provides a comprehensive overview of separate as well as simultaneous CO and CH4 oxidation reactions for CNG vehicular emission control. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Green fuel; CNG vehicle; CO-CH4 emission; Catalytic control; Spinel catalyst